Optimizing Bappeda Performance in the Development Planning Process in Medan City in 2021 - Fanny Fanny; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine and describe the performance of Bappeda in the role of Regional Development Planning. and to find out how to optimize the performance of Bappeda in regional development. This research is located at BAPPEDA PEMKO MEDAN. This research uses descriptive research. Sources of data collection is done with primary data and secondary data through in-depth interviews. And using data collection methods through observation and documentation. BAPPEDA is a supporting element of the Mayor led by a Head of Agency who is under and responsible to the Mayor of Medan, BAPPEDA is in charge of implementing the implementation of regional policies in the field of urban planning. Bappeda as an element of state administrators has an obligation to carry out its main tasks and characteristics, one of which is manifested in the preparation of performance reports of government agencies that support the mayor's vision, namely